A university extension course in leprosy: telemedicine in the Amazon for primary healthcare - Paixao, Mauricio Pedreira; Miot, Hélio Amante [UNESP]; de Souza, Pedro Elias; Haddad, Ana Estela; Wen, Chao Lung (Royal Soc Medicine Press Ltd, 2009)
There is a high prevalence of leprosy in the Amazon region of Brazil. We have developed a distance education course in leprosy for training staff of the Family Health Teams (FHTs). The course was made available through a web portal. Tele-educational resources were mediated by professors and coordinators, and included the use of theoretical content available through the web, discussion lists, Internet chat, activity diaries, 3-D video animations (Virtual Human on Leprosy), classes in video streaming and case simulation. Sixty-five FHT staff members were enrolled. All of them completed the course and 47 participants received a certificate at the end of the course. At the end of the course, 48 course-evaluation questionnaires were answered. A total of 47 participants (98%) considered the course as excellent. The results demonstrate the feasibility of an interactive, tele-education model as an educational resource for staff in isolated regions. Improvements in diagnostic skills should increase diagnostic suspicion of leprosy and may contribute to early detection.